A New Method for Obtaining Radar Images of Concealed Objects in Microwave Personnel Screening Systems - Zhuravlev, Andrey; Razevig, Vladimir; Chizh, Margarita; Dong, Ge; Hu, Boxiong (IEEE transactions on microwave theory and techniques, 2021)
In modern microwave personnel screening systems, a 2-D synthetic aperture is used to obtain a radar image with resolution limited by the diffraction of electromagnetic waves. Therefore, the antenna system of the screening system has large dimensions, a large number of switched channels, and a high cost, which limits a wider use of these systems, for example, at ground transport hubs or administrative buildings. In this article, we consider a different method of forming synthetic aperture, in which it is formed due to the relative movement of a subject near a stationary antenna system. Using the described experimental setup and imitation experiment with a mannequin, it was shown that the proposed method can significantly reduce the dimensions of a prospective screening system and the number of channels in the antenna system and at the same time obtain detailed radar images of hidden objects.